Molecular diagnosis of infectious diseases - Decker, Jochen,et al.,Ed (Humana Press, 2004)
Populations of the western world are now healthier and enjoying higher life expectancy than ever. They are beginning to benefit from an array of costly new therapies made possible through recent rapid advances in medical science and technology, and their demands on modern medicine are rising. Meanwhile, healthcare systems are struggling with their outdated legacy models of the m- th 20 century and are experiencing ever-increasing financial pressure from g- ernments and health insurance organizations. The equation is no longer in balance, and this predicament is forcing societies to explore new approaches to managing healthcare in the future. Since the first edition of Molecular Diagnosis of Infectious Diseases was published, we have witnessed the sequencing of the (almost) complete human genome and a shift in medical research from an emphasis on genetics to the advancement and useful application of proteomics. Bioinformatics has become the key tool for managing and analyzing the upsurge of data, and faster and more effective test methods and technologies have opened up new prospects for ind- try and academia. The tools of modern genomics and proteomics are now being utilized to specifically guide the discovery of drugs for the prevention, diagnosis, and treatment of human disease. They may also help us to find a way out of the current healthcare calamity.